Effect of Nutrient Solution Temperature and Varieties on Growth and Yield of Lettuce (Lactuca sativa L.) with Nutrient Film Technique System - Rachman, Aulia Afifah; Kusumiyati, Kusumiyati; Sutari, Wawan; Shazma AnwarÂ (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Lettuce plants are cool-season leaf vegetables, if grown in areas near the city center with high temperatures can reduce the quantity and quality of the yield. The low temperature in the root zone in the hydroponic system was the solution. This experiment aimed to determine the effect of nutrient solution temperature and variety on the growth and yield of lettuce plants in the nutrient film technique (NFT) system. The experimental design used was a Randomized Block Design with 6 treatments (a combination of solution temperatures 25, 16, and 10 â„ƒ; Red and Green lettuce). The result showed no significant effect of the treatment on the number of leaves 0-20 days after planting (DAP) and root length. Nutrient solution temperature +10 â„ƒ gave the best response to the number of leaves (13.08 sheets), plant height (20.80 cm), root volume (18.88 mL), and fresh weight (137.08 g) of green lettuce plants.